Financing Higher Education and Economic Development in East Asia - Armstrong, Shiro (ANU Press, 2011)
This volume addresses important issues to do with access to higher education and different models of its financing in the East Asia region. It is enriched by diverse perspectives from vastly different starting points and by the historical and institutional settings in the region. The issues are set out in the context of the value of higher education in economic development and how it contributes to the capacities to adopt and adapt to new technologies and undertake institutional innovation. The established and well-functioning higher education loan and financing systems, such as those in Australia, and the experience of different systems tried-both in East Asia and in the United States-are brought to bear in this volume.